Handbook of research on digital research methods and architectural tools in urban planning and design - Abusaada, Hisham, 1956-; Vellguth, Carsten, 1960-; Elshater, Abeer, 1976- (Advances in civil and industrial engineering (ACIE) book series., 2019)
"This book investigates new and pragmatic methods concerning the impacts of contemporary digital technology in the field of architecture, with a focus on urban planning and design disciplines"--